Analysis of the Impact of Import Tax Increases on Business Income in Timor Leste - Agostinho Coelho; Antonio B. Carcerres; Mateus Pinto (Greenation Research & Yayasan Global Resarch National, 2025)
Fiscal policy, particularly import tax policy, plays a crucial role in a country's economic stability, particularly for developing countries like Timor-Leste, which still rely heavily on imported goods. Import tax increases can have significant consequences for business activities, particularly in terms of cost structure, selling prices, and corporate revenue. This study is a literature review aimed at conceptually analyzing the impact of import tax increases on business revenue. The method used is a literature review of various sources, such as scientific journals, government reports, and relevant economic publications. The results of the study indicate that increases in import tariffs generally tend to increase production input prices, reduce product competitiveness, and reduce corporate profit margins, ultimately resulting in decreased business revenue. However, in some contexts, such policies can also encourage businesses to switch to local products and improve operational efficiency. Thus, the effect of import tax increases on business revenue is highly dependent on the readiness of businesses to adapt and domestic market conditions. This study provides a theoretical basis for further empirical research and can be used as a consideration by the Timor-Leste government in formulating a more balanced tax policy between fiscal needs and business sustainability.